Preparation and Photoluminescence of Transparent Poly(methyl methacrylate)-Based Nanocomposite Films with Ultra-High-Loading Pendant ZnS Quantum Dots - Jinku Xu (Polymers, 2018)
Transparent nanocomposite films containing quantum dots are popular because of their extensive applications. However, nanoparticles tend to aggregate, resulting in phase separation of the nanoparticles in the polymer matrix. Herein, we present a bulk thermo-curing copolymerization method to fabricate poly(methyl methacrylate)-based nanocomposite films with ultra-high-loading ZnS quantum dots (ZnS/PMMA), utilizing polymerizable group-capped ZnS and monomer of methyl methacrylate (MMA). We found that the nanocomposite film is highly transparent, although the transmittance decreases with the ZnS content, especially at the wavelength between 300 nm and 400 nm. The results from X-ray diffraction (XRD), transmission electron microscopy (TEM), and dynamic mechanical thermal analysis (DMTA) show that the ZnS quantum dots maintain their original crystal structure, and are uniformly dispersed in the nanocomposite films, even with a very high ZnS content (41 wt %, determined by thermogravimetric analysis). The thermogravimetric analysis shows that the nanocomposite films possess a better thermal stability than that of pure PMMA film. The photoluminescence measurements show that ZnS/PMMA nanocomposite films have good optical properties. The fluorescence intensity increases with the increment of free ZnS content to 30 wt %, and then decreases due to self-reabsorption at a higher ZnS content. The transparent ZnS/PMMA nanocomposite films have a potential application as photoluminescence material.